Seasonal Abundance of Adult Beetles Species on the Exposed Carcasses in Baghdad City - – Rassoul, M .S . Abdul; Augul, R. SH.; Al – Saffar, H. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Beetles specimens were collected from exposed animal carcasses in Baghdad city; and prepared for farther taxonomic study. The investigation started from February2006 till January 2007.The results obtained showed that beetles could be collected during late winter to early autumn with variation of their population density at different seasons. The majority of the collected species were abundant during spring and early summer. In this investigation, four species confined to three families were identified. The species Saprinus sp . 1 (family: Histeridae) was the most abundant followed by Dermestes maculates  De Geer ( family : Dermestidae ) , while Saprinus sp . 2 and Necrobia rufipes (De Geer) (family: Cleridae ) were the least abundant species .